THE EFFECT OF A GENRE-BASED PEDAGOGICAL APPROACH ON ORANG ASLI STUDENTS’ EFL WRITING PERFORMANCE (Malaysian Journal of Learning and Instruction, 2022)
Purpose – In the 21st century, the importance of having good English proficiency in Malaysia and globally has impacted educators, especially in terms of their pedagogical practices. Although students are exposed to 11 years of English language instruction in Malaysia, Orang Asli students still possess low English proficiency and poor writing skills. This study aims to determine the extent to which the genre-based pedagogical approach is able to improve Orang Asli students’ English as a foreign language (EFL) writing performance and analyse their responses in using the genre-based pedagogical approach as a framework to improve their EFL writing performance.Methodology – This quasi-experimental study included 78 students from a secondary school in Pahang, Malaysia. Participants were assigned to the experimental and control groups (N=39) to generate students’ pretest and posttest scores. Quantitative data from the students’ questionnaire were also triangulated with qualitative data from the focus group discussions with the experimental group. Findings – The approach was effective in improving students’ descriptive writing and had a more significant effect than the mainstream process-based approach. Students reacted positively to the approach as they found it useful in improving their writing skills, which correlated with their improved test scores. Therefore, the genre-based pedagogical framework can be further enhanced by incorporating more grammar-related activities to meet the learning needs of Orang Asli students lacking in EFL writing skills.Significance – The novelty of this study is that the framework has the potential to be implemented in Malaysian secondary schools and other indigenous’ educational contexts. Furthermore, this study can be a point of reference to stakeholders, English language teaching (ELT) practitioners and educators in terms of advocating a genre-based pedagogical approach in an EFL context.